Adipofascial fold-down flaps based on the posterior tibial artery perforator to cover the medial foot and ankle defects. Issue 12 (December 2016) - Lee, K.J.; Lee, S.H.; Kim, M.B.; Lee, Y.H.
Summary: Purpose: We report the clinical outcome after coverage for soft-tissue defect on the medial foot and ankle with an adipofascial fold-down flap based on the posterior tibial artery perforator branch proximal to the defect. Materials: Nine patients (five males and four females) with soft-tissue defects on the medial foot and ankle area underwent the procedure from March 2009 to May 2014. The average age of the patients was 54 years (range, 8–82). The pivot point of transposition of this flap is the posterior tibial artery perforator proximal to the defect. Therefore, the adiposal side of this flap was folded down to resurface the defect. The donor site was closed primarily with the preserved skin flap. The skin graft to the flap was delayed until the flap became mature. The difference between the circumferences of both ankles was measured. Results: All flaps survived and adequate soft-tissue coverage was obtained for the medial foot and ankle after the skin graft. Wearing normal footwear was possible for all patients because of thin coverage of the flaps. No secondary debulking procedure was performed for the patients. The difference between the circumferences of both sides of the ankle was not significant. The skin necrosis of the donor site was also managed conservatively and healed well. Conclusion: For the medial foot and ankle soft-tissue defect, the fold-down adipofascial flaps based on the posterior tibial artery perforator branch proximal to the defect could be a good option to cover it.